France. (December 2014) - Drake, Helen
<x xml:space="preserve">Abstract</x> France's economy is struggling, the far‐right Front National is gaining ground and former President Nicolas Sarkozy wants to return to 'save' the country from itself. Helen Drake examines whether France can restore its reputation as a global economic player and a democratic beacon. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>